Potensi Hilangnya Hak Demokrasi Masyarakat IKN Terkait Sistem Pemilihan Kepala Otorita IKN dalam Undang-Undang Nomor 3 Tahun 2022 - Nur Badrotin Jabbar, Achmad Arbi; Yasin, Ikhsan Fatah (Universitas Bojonegoro, 2025)
The existence of the Head of the Ibu Kota Negara Authority, as regulated by Law of the Republic of Indonesia Number 3 of 2022 (UU No. 3 of 2022), has given rise to significant legal issues. The mechanism for the appointment, dismissal, and termination of the Head of the Authority, carried out directly by the President, is considered contrary to the democratic principles enshrined in Article 18 of the 1945 Constitution of the Republic of Indonesia, which emphasizes the importance of democratically electing regional heads. Additionally, the status of the Head of the Authority, which is equivalent to a minister, raises questions regarding the position and legitimacy of the legal products issued by this authority. This research adopts a normative legal method to analyze the constitutional implications of this regulation. The findings indicate a potential constitutional violation regarding the existence and appointment mechanism of the Head of the Authority under UU No. 3 of 2022, which could affect the democratic rights of the community, particularly in the Ibu Kota Nusantara (IKN) region. In this context, it is crucial to reconsider the existing regulations to ensure that democratic principles and community rights are upheld. Therefore, further studies are necessary to evaluate the impact of these regulations on governance practices and community participation in decision-making processes, as well as to develop policy recommendations that support the sustainability of regional autonomy and decentralization principles. Thus, the existence of the Head of the Authority should align with the goal of establishing a democratic and responsive government that meets the aspirations of local communities.